A multifunctional nanoparticulate theranostic system with simultaneous chemotherapeutic, photothermal therapeutic, and MRI contrast capabilities. Issue 33 (16th March 2016) - Zhang, Ming; Yilmaz, Turker; Boztas, Ali Ozgur; Karakuzu, Ozgur; Bang, Woo Young; Yegin, Yagmur; Luo, Zhiping; Lenox, Mark; Cisneros-Zevallos, Luis; Akbulut, Mustafa
Abstract : Herein, a single-step, scalable approach for preparing a multifunctional, theranostic drug delivery system made out of paclitaxel, iron oxide nanoparticles, gold nanoparticles, and poly(ethylene oxide)- b -poly(ε-caprolactone) is reported. Abstract : Multifunctional nanomedicines with imaging and multimodal therapies have become a new trend in the current development of cancer therapy. Herein, we report the use of a Flash NanoPrecipitation approach for fabricating a multifunctional nanoparticulate theranostic system (MNTS) simultaneously encapsulating paclitaxel, gold nanoparticles, and iron oxide nanoparticles in poly(ethylene oxide)- block -poly(ε-caprolactone) (PEO- b -PCL). The combination of these building blocks in a single system translates into an advance nanomedicine with concurrent chemotherapeutic, photothermal therapeutic, and MRI contrast properties. Using dynamic light scattering, the hydrodynamic diameter of MNTS was found to range from 50 nm to 500 nm with the mean size of 190 ± 14 nm. The co-localization of paclitaxel, gold nanoparticles, and iron oxide nanoparticles were confirmed via scanning- and cryo-transmission electron microscopy. At a paclitaxel concentration of 100 pM, the cell viability after a 72 h treatment of MNTS was 35 ± 3% and 31 ± 1% for MCF-7 and MDA-MB-231 cell lines, respectively while that of bare paclitaxel was 77 ± 2% and 91 ± 3%, respectively. Irradiation of MNTS with a 200 mW laser (532 nm) for 5 min during the treatment stage resulted in a further 20% and 226% decrease in the viability of MCF-7 and MDA-MB-231, respectively. MRI relaxivity measurements revealed that the T 2 relaxation times of MNTS was 47 ± 5 ms and significantly different from that of most human anatomical parts susceptible to cancer.